Cardiac troponin T estimation post elective stent implantation and prediction of early and late outcomes - R., Baiju; Viswanathan, Sunitha; K. K., Sarosh Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Coronary artery disease (CAD) is a major cause of mortality and morbidity. Per Cutaneous Interventions (PCI) is emerging as the mainstay of treatment for CAD. Periprocedural myocardial necrosis, which can range from a low-level elevation of cardiac biomarkers to a large myocardial infarction, is an important complication of PCI. There are conflicting reports regarding peri-procedural biomarker elevation and adverse outcome. It is in this context we have undertaken this study to assess the prognostic significance of cardiac troponin T elevation after elective stent implantation. Methods: The study population included 100 consecutive patients who underwent elective PCI with stent implantation in cardiology unit of Medical College, Trivandrum. Serial cardiac enzyme levels were measured in all patients undergoing the procedure. CPK was measured at 8 hrs, 16 hrs and 24 hrs and Troponin T was measured at 8hrs and 24 hrs. post PCI. In hospital events were documented and patients were on follow up for a period of 1 year. Primary endpoints of death, myocardial infarction, recurrent ischemia leading to revascularization were noted. Results: In our study population of 100 patients there were 87 males and 13 females. Among them 50% had unstable angina, 18% had exertional angina and 32% were post myocardial infarction patients. In this group of hundred patients 79% had single vessel disease, 18% had two vessels and 3% had triple vessel disease. A total of 103 stents were deployed. Mean CPK levels were CPK-1 (80.11+36.19), mean CPK-2 (83.91± 34.8) and mean CPK-3 (86.32+57.80). Mean Troponin T-1 was 0.04+0.1 and mean Troponin-2 was 0.06+0.145. In this study, we compared late onset angina with Troponin and CPK positivity and found that both Troponin-1 & Troponin-2 had significant correlation with late onset angina. Conclusions: Periprocedural Troponin T is more sensitive than CPK in predicting late events. Thrombus containing lesions and bifurcation lesions were significantly associated with elevation in Troponin T. No significant Troponin T elevations were noted in patients with diabetes mellitus and those containing calcified lesions. Drug eluting stents were associated with a relatively lesser Troponin T elevations but not statistically significant.